Relationships between polycyclic aromatic hydrocarbons, small dust grains, H2, and H I in local group dwarf galaxies NGC 6822 and WLM using JWST, ALMA, and the VLA - Chown, Ryan; Leroy, Adam K.; Bolatto, Alberto D.; Chastenet, Jérémy; Glover, Simon; Indebetouw, Rémy; Koch, Eric W.; Donovan Meyer, Jennifer; Pingel, Nickolas M.; Rosolowsky, Erik; Sandstrom, Karin; Sutter, Jessica; et al. (The astrophysical journal, 2025)
We present 0.6-3.2 pc resolution mid-infrared (MIR) JWST images at 7.7 μm (F770W) and 21 μm (F2100W) covering the main star-forming regions of two of the closest star-forming low-metallicity dwarf galaxies, NGC 6822 and Wolf-Lundmark-Melotte (WLM). The images of NGC 6822 reveal filaments, edge-brightened bubbles, diffuse emission, and a plethora of point sources. By contrast, most of the MIR emission in WLM is pointlike, with a small amount of extended emission. Compared to solar-metallicity galaxies, the ratio of 7.7 μm intensity (), tracing polycyclic aromatic hydrocarbons (PAHs), to 21 μm intensity (), tracing small, warm dust grain emission, is suppressed in these low-metallicity dwarfs. Using Atacama Large Millimeter/submillimeter Array CO(2-1) observations, we find that detected CO intensity versus at ≈2 pc resolution in dwarfs follows a similar relationship to that at solar metallicity and lower resolution, while the CO versus relationship in dwarfs lies significantly below that derived from solar-metallicity galaxies at lower resolution, suggesting more pronounced destruction of CO molecules at low metallicity. Finally, adding in Local Group L-Band Survey 21 cm H i observations from the Very Large Array, we find that and versus total gas ratios are suppressed in NGC 6822 and WLM compared to solar-metallicity galaxies. In agreement with dust models, the level of suppression appears to be at least partly accounted for by the reduced galaxy-averaged dust-to-gas and PAH-to-dust mass ratios in the dwarfs. Remaining differences are likely due to spatial variations in dust model parameters, which should be an exciting direction for future work in local dwarf galaxies.
Veröffentlicht: 1. Juli 2025
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 11.11.2025